The E2 transactivator of bovine papillomavirus type 1 is expressed from multiple promoters. - Vaillancourt, P (1990)
The E2 proteins of bovine papillomavirus type 1 (BPV-1) are a family of site-specific DNA-binding proteins which regulate viral transcription by repression and activation. Repressors E2-TR and E8/E2 are expressed from promoters P5 (P3080) and P3 (P890), respectively. Previous reports have provided evidence that the transcript for the 48-kilodalton transactivator is initiated from a promoter proximal to the open reading frame encoding this protein (P2440 or P4). Our studies extend these findings and show that the E2 transactivation gene is expressed from multiple promoters. We have described the isolation of a cDNA (N15-2) which represents an RNA species expressed from the P3 promoter. The major exon of this species was produced by splicing to an acceptor located at nucleotide 2558 and contained the complete E2 open reading frame. The acceptor is probably utilized by yet another more abundant mRNA expressed from the P2 promoter (A. Stenlund, J. Zabielski, H. Ahola, J. Moreno-Lopez, and U. Pettersson, J. Mol. Biol. 182:541-554, 1985). Linked to a surrogate promoter, the N15-2 cDNA can transactivate an E2-responsive reporter gene. BPV-1 plasmids containing mutations either in the 2558 splice acceptor or in the P4 promoter showed significantly reduced transforming ability and reduced ability to transactivate an E2-responsive reporter, while a double mutant was inactive in both assays. The transformation defect was complemented by an E2 expression vector, and the BPV genome absolutely required the E2 protein to transactivate in the second assay. Thus, these genetic experiments show that alternate modes of E2 expression contribute to the E2 mRNA pool. Direct analysis of cytoplasmic RNA from transformed cultured cells proves that transcripts containing the 2558 acceptor exon are approximately as abundant as the P4 type E2 mRNAs. Furthermore, analysis of the E2 proteins present in various cell lines harboring specific BPV-1 mutants, including the 2558 acceptor mutant, proves that alternate modes of E2 expression exist. The ability of the E2 activator and repressors to each be independently expressed from multiple E2-responsive promoters probably adds to the resiliency of the latent virus as a plasmid and may be important for its homeostasis within the cell in different environmental or developmental situations.